A cross-sectional study of the Birmingham Vasculitis Activity Score version 3 in systemic vasculitis. - Suppiah, R; Mukhtyar, C; Flossmann, O; Alberici, F; Baslund, B; Batra, R; Brown, D; Holle, J; Hruskova, Z; Jayne, DR; Judge, A; Little, M; et al. (2011)
OBJECTIVE: Assessment of disease activity in vasculitis can be achieved using the BVAS, a clinical checklist of relevant symptoms, signs and features of active disease. The aim of this study was to revalidate the BVAS version 3 (BVAS v. 3) in a cohort of patients with systemic vasculitis. METHODS: A total of 238 patients with vasculitis from seven countries in Europe were evaluated at a single time point. Spearman's correlation coefficients were calculated between BVAS v. 3 scores, vasculitis activity index (VAI), physician's global assessment (PGA), the physician's treatment decision, CRP and the vasculitis damage index (VDI) to demonstrate that the BVAS v. 3 measures disease activity. RESULTS: WG (63%), Churg-Strauss syndrome (9%) and microscopic polyangiitis (9%) were the most common diagnoses. The BVAS v. 3 showed convergent validity with the VAI [ρ = 0.82 (95% CI 0.77, 0.85)], PGA [ρ = 0.85 (95% CI 0.81, 0.88)] and the physician's treatment decision [ρ = 0.54 (95% CI 0.44, 0.62)]. There was little or no correlation between BVAS v. 3 and the CRP level [ρ = 0.18 (95% CI 0.05, 0.30)] or with the VDI [ρ = -0.10 (95% CI 0.22, 0.03)]. The inter-observer reliability was very high with an intra-class correlation coefficient (ICC) of 0.996 (95% CI 0.990, 0.998) for the total BVAS v. 3 score. CONCLUSION: The BVAS v. 3 has been evaluated in a large cohort of patients with vasculitis and the important properties of the tool revalidated. This study increases the utility of the BVAS v. 3 in different populations of patients with systemic vasculitis.